Entre el Consejo de Solón y el de Clístenes:¿Heliea en época de Pisístrato? - Valdés Gula, M¡riam (Gerión. Revista de Historia Antigua, 2003)
In these pages we consider the possibility of some kind of continuity between Solonian and Cleisthenic Boule, over all in its hypothetical judicial function as Heliaia in the time of the tyranny. The Peisistratid government supported by the Attic demos, promoted a more unified and stronger sense of citizenship which favoured the resistance and the victory of the Athenian people over Cleomenes and Isagoras; this took place at the end of dm Sixth Century B.C. under the leadership of the Council and before Cleisthenes returned from his exile.